Impact of elexacaftor-tezacaftor-ivacaftor in lung transplantation for cystic fibrosis in the United States - Tahuanty A. Pena, MD, MS; Brittany Wright, PharmD; Kalpaj R. Parekh, MBBS; Julia Kleney-Tait, MD, PhD (JHLT Open)
Background: Cystic fibrosis (CF) is an autosomal recessive condition leading to progressive lung disease and often necessitating lung transplantation. Historically, CF has been one of the leading indications for lung transplants in the United States. The advent of CF transmembrane conductance regulator (CFTR) modulators, particularly elexacaftor-tezacaftor-ivacaftor (ETI), has significantly improved clinical outcomes for people with CF (pwCF), offering potential alterations in disease progression and transplantation needs. Methods: Data on lung transplants performed in the United States since 1988 were retrieved from the Organ Procurement & Transplantation Network. Custom reports were generated to compare the number of lung transplants and waitlist additions before and after ETI approval in 2019. The analysis focused on trends from 2009-2019 (pre-ETI) and 2021-2023 (post-ETI). Results: The average annual lung transplants for CF decreased significantly from 243 (2009-2019) to 56.7 (2021-2023) post-ETI approval. Similarly, the average number of pwCF added to the lung transplant waitlist per year dropped from 295 to 55.6. Despite an overall increase in lung transplants and waitlist additions in the United States, the proportion involving pwCF has markedly declined post-ETI. Conclusions: The introduction of ETI has dramatically reduced the need for lung transplants among pwCF, reflecting significant improvements in lung function and disease management. These findings underscore the transformative impact of CFTR modulators like ETI on the natural history of CF, highlighting the importance of continued advancements in precision medicine for genetic disorders. Future studies should investigate long-term outcomes and sustained trends in lung transplantation needs among pwCF.